Market Power, International CO₂ Taxation and Petroleum Wealth - Elin Berg; Snorre Kverndokk; Knut Einar Rosendahl (Statistics Norway, Research Department, 1996)
This paper studies the effects on fossil fuel prices, extraction paths and petroleum wealth of an international carbon tax on fossil fuel consumption. We present an intertemporal equilibrium model for fossil fuels, where the main focus is on the oil market. The impacts of a global carbon tax of 10 per barrel of oil depend heavily on the market structure in the oil market. If OPEC acts as a cartel, they reduce their production to maintain the oil price. Thus, the effects on the oil wealth of the competitive fringe is minor, while OPEC's oil wealth is considerably reduced. This may explain the difference in attitudes of OPEC and other oil producing countries to international global warming negotiations. If, on the other side, the oil market is competitive, the highest relative reductions in the oil wealth are to be found among non-OPEC producers.
Keywords: H23; Q30; Q40; 330; International Carbon Taxes; Exhaustible Resources; Petroleum Wealth.